Chilhood Trauma as a Pathway to Moral Growth: Elsa’s Story in Frozen (2013) - Candranaya, Cahyarani Kartika; Candraningrum, Dewi (Lingua Susastra, 2025)
This study examines childhood trauma as a catalyst for moral growth in the character of Elsa from Disney's Frozen (2013). Using qualitative descriptive methods, this study analyzes dialogues, scenes, and visual symbols that depict Elsa's psychological conflicts, emotional repression, and moral transformation. This study undertakes a qualitative textual analysis of Frozen (2013), with a major focus on key scenes and dialogues depicting trauma and moral evolution. Synthesizing the trauma theory by Caruth, the recovery model by Herman, embodied healing by Van der Kolk, and moral frameworks by Kohlberg, Gilligan, and Tedeschi Calhoun, the thesis shall trace how psychological suffering advances into ethical growth. This analysis reveals that Elsa's experiences of fear, guilt, and isolation develop into empathy, accountability, and compassion, demonstrating the transformative role of trauma in shaping moral consciousness. These findings suggest that moral growth emerges through a process of acknowledging and integrating trauma rather than avoiding it. Furthermore, this study describes how children's animated films, particularly Frozen, can function as cultural narratives that reflect psychological realities and foster an understanding of resilience and ethical maturity. This paper addresses the gap in the literature by integrating trauma and moral development theories in proposing a new interpretive model that explains how animated trauma narratives foster moral and emotional literacy.